IMPROVING TOEFL SCORES THROUGH STRUCTURED ONLINE COACHING AND MOBILE APPLICATIONS: CLASSROOM ACTION RESEARCH - Al Qadrie, Imam Hidayatullah; Yuliana, Yohanes Gatot Sutapa; Susilawati, Endang (FKIP - Universitas Tanjungpura, 2026)
Healthcare students at Poltekkes Pontianak face significant challenges in achieving the mandated TOEFL score of 400 necessary for graduation. This classroom action research investigated the effectiveness of integrating structured online coaching with mobile-assisted language learning (MALL) applications to enhance TOEFL preparation outcomes. The study employed Kemmis and McTaggart's cyclical action research model over 12 weeks, involving 30 healthcare students. Data collection included pre-, mid-, and post-tests, mobile application engagement logs, reflection journals, and focus group discussions. Quantitative data were analyzed using paired sample t-tests and Pearson correlation analysis, while qualitative data underwent thematic coding. Results indicated significant improvements in TOEFL performance, with mean scores increasing from 332.17 (SD=11.24) to 397.67 (SD=15.83), representing a gain of 65.50 points (t(29)=28.45, p